1983
DOI: 10.1104/pp.72.4.919
|View full text |Cite
|
Sign up to set email alerts
|

Differential Leakage of Intracellular Substances from Imbibing Soybean Seeds

Abstract: Leakage of electrolytes, substances absorbing UV light, and enzymic activities from imbibing soybean (Glycine max IL.I Menf.) seeds were compared to determine the extent that passive diffusion and cellular rupture contribute to each. Imbibing seeds with testae removed had average Arrhenius energies of activation (5 to 25°C) of 3.0 and 15.8 kilocalones per mole, respectively, for the leakage of electrolytes and embryo malate dehydrogenase activity. Leakage of embryo enzymes from imbibing seeds was dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 22 publications
3
31
0
1
Order By: Relevance
“…Because the whole SE and HP of SE displayed an almost equal potential for rhizobium proliferation, the compounds in LP and HW fractions of SE appeared to display a negligible potential. It was reported that imbibing soybean seeds leaked out high molecular materials mainly from the physically damaged cotyledon and diffused out low-molecular substances from the seed coat (Simon 1974;Duke et al 1983). Almost the same amount of secreted sugars and amino acids was observed in a comparative examination of whole seeds and isolated soybean seed coats (data not shown), suggesting that most of the low molecular materials in the SE were derived from seed coats.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Because the whole SE and HP of SE displayed an almost equal potential for rhizobium proliferation, the compounds in LP and HW fractions of SE appeared to display a negligible potential. It was reported that imbibing soybean seeds leaked out high molecular materials mainly from the physically damaged cotyledon and diffused out low-molecular substances from the seed coat (Simon 1974;Duke et al 1983). Almost the same amount of secreted sugars and amino acids was observed in a comparative examination of whole seeds and isolated soybean seed coats (data not shown), suggesting that most of the low molecular materials in the SE were derived from seed coats.…”
Section: Discussionsupporting
confidence: 48%
“…Though the root exudate should be considered as a factor affecting root nodulation, seedreleased compounds may strongly affect rhizobium infection and nodule formation immediately after rooting and germination. Duke et al (1983) suggested that imbibing soybean seeds exuded macromolecules from ruptured embryo cells and low molecules by negative diffusion. Although it has been reported that pathogen growth was enhanced by seed leachates (Schroth and Cook 1964;Nelson and Craft 1989), there are only few studies on the effect of seed exudates on rhizobium proliferation.…”
mentioning
confidence: 99%
“…The contents of sugars and amino acids (pmol g-'-seed weight) were calculated by using the average weight of a seed (Hokkaikintoki, 0.65 g; Himetebou, 0.36 g; Kurodanekinugasa, 0.19 g) reported previously , and the respective values of the sugars and amino acids decreased in the order of Kurodanekinugasa (12.47 and 2.24), Himetebou (12.17 and 1.37) and Hokkaikintoki (7.49 and 0.69). It was reported that nutrient leakage from imbibing soybean seeds depended on passive water-diffusion and cellular rupture of the cotyledon (Duke et al 1983), and that water absorption by a small seed was more rapid than that by a large one (Calero et al 1981;Horings et al 1991). Since the seed size of Kurodanekinugasa is the smallest, the contents of sugars and amino acids in the seed exudates of Kurodanekinugasa were considered to have become the highest among the three cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in spite of many attempts in various laboratories, phosphorylating mitochondria ofgerminating seeds have been obtained in only two cases, from peanut cotyledons imbibed for 40 min (27), and from cucumber cotyledons imbibed for 6 h (14). Moreover, the leakage of solutes during seed imbibition suggested some degree of membrane disorganization either in the dry state or following rehydration (5,23,26). It was believed, in particular, that mitochondria were damaged and had to be repaired during the germination period to become functional at the time of radicle emergence (13).…”
Section: Plant Materialsmentioning
confidence: 99%